Meeting the new challenges : report...on the implementation of the 1995 Commonwealth Plan of Action on Gender and Development (Commonwealth Secretariat LondonGB, 2001)
Provides a wealth of information and examples of good practice from countries in advancing the gender agenda and identifies areas for future action. Provides a brief summary of recent experiences and progress within individual Commonwealth countries. Focuses on the gender mainstreaming programme, and highlights action taken by National Women's Machineries and useful lessons learned.
Keywords: GENDER ROLES